Let it be me [large type] - Wade, Becky (Wade, Becky. Misty River romance, 2021)
"The one woman he wants is the one he cannot have. Former foster kid Sebastian Grant has leveraged his intelligence and hard work to become a pediatric heart surgeon. But not even his career success can erase the void he's tried so hard to fill. Then he meets high school teacher Leah Montgomery and his fast-spinning world comes to a sudden stop. He falls hard, only to make a devastating discovery--Leah is the woman his best friend set his heart on months before.Leah's a math prodigy who's only ever had one big dream--to earn her PhD. Raising her little brother put that dream on hold. Now that her brother will soon be college bound, she's not going to let anything stand in her way. Especially romance . . . which is far less dependable than algebra.When Leah receives surprising results from the DNA test she submitted to a genealogy site, she solicits Sebastian's help. Together, they comb through hospital records to uncover the secrets of her history. The more powerfully they're drawn to each other, the more strongly Sebastian must resist, and the more Leah must admit that some things in life--like love--can't be explained with numbers"--